2002
DOI: 10.1080/13546800244000003
|View full text |Cite
|
Sign up to set email alerts
|

Time course of inhibition and facilitation in patients with schizophrenia

Abstract: These results suggest that schizophrenia patients are better able to inhibit irrelevant stimuli that are immediate, but the sustainment of inhibition across very short time intervals (500 ms) may fade compared to controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 69 publications
2
10
0
Order By: Relevance
“…31, 45, 55-58 In several of these studies, SZ patients showed more facilitation than normal controls, but no difference in RT interference 31, 59 . Similar findings of equivalent Stroop RT interference in SZ patients have also been reported in priming experiments that used Stroop stimuli, 38, 46, 60, 61 and in neuroimaging studies 62, 63 . Other studies that have measured top-down behavioral control have also failed to find deficits in SZ patients 64 .…”
Section: Discussionsupporting
confidence: 84%
“…31, 45, 55-58 In several of these studies, SZ patients showed more facilitation than normal controls, but no difference in RT interference 31, 59 . Similar findings of equivalent Stroop RT interference in SZ patients have also been reported in priming experiments that used Stroop stimuli, 38, 46, 60, 61 and in neuroimaging studies 62, 63 . Other studies that have measured top-down behavioral control have also failed to find deficits in SZ patients 64 .…”
Section: Discussionsupporting
confidence: 84%
“…Other behavioral studies have provided evidence for increased interference independent of general slowing (for review see Henik and Salo, 2004). The inconsistent findings might be related to methodological differences (as intertrial interval) or subjects investigated (Hepp et al, 1996;Salo et al, 2002). For example, patients with the paranoid subtype might exhibit increased interference (Carter et al, 1993).…”
Section: Discussionmentioning
confidence: 95%
“…In turn, this should lead to facilitation being greater than interference. By contrast, the general finding on this issue is that the facilitation effect is much smaller than the interference effect (Glaser & Glaser, 1989;Ikeda, Okuzumi, & Kokubun, 2013;MacLeod, 1991;Schmidt & Besner, 2008;Sugg & McDonald, 1994).…”
Section: Validity Of Stroop Tasks For Assessing Automaticitymentioning
confidence: 89%